2015
DOI: 10.1016/j.bpj.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Redox Regulation of Ca2+ Signaling and Viability in Normal and Malignant Prostate Cells

Abstract: In prostate cancer, reactive oxygen species (ROS) are elevated and Ca(2+) signaling is impaired. Thus, several novel therapeutic strategies have been developed to target altered ROS and Ca(2+) signaling pathways in prostate cancer. Here, we investigate alterations of intracellular Ca(2+) and inhibition of cell viability caused by ROS in primary human prostate epithelial cells (hPECs) from healthy tissue and prostate cancer cell lines (LNCaP, DU145, and PC3). In hPECs, LNCaP and DU145 H2O2 induces an initial Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 63 publications
(69 reference statements)
0
24
0
Order By: Relevance
“…Clearly, the source of ROS, levels and duration of this redox signal will determine the eventual impact on SOCE. For example, domains of localized ROS production at the ER and mitochondria may exclusively affect SOCE via redox activation of STIM1 and hence lead to pro-tumorigenic Ca 2+ signaling, while exogenous redox stress sensed by plasma membrane localized ORAI channels may block SOCE and attenuate proliferation of tumor cells and also make tumor cells more susceptible to redox stress (Figure 7) [198]. It is also possible that ROS mediate STIM translocation and SOCE activation indirectly, through redox activation of ER Ca 2+ regulators IP 3 R and SERCA, which are also redox sensitive (See section 4).…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
See 4 more Smart Citations
“…Clearly, the source of ROS, levels and duration of this redox signal will determine the eventual impact on SOCE. For example, domains of localized ROS production at the ER and mitochondria may exclusively affect SOCE via redox activation of STIM1 and hence lead to pro-tumorigenic Ca 2+ signaling, while exogenous redox stress sensed by plasma membrane localized ORAI channels may block SOCE and attenuate proliferation of tumor cells and also make tumor cells more susceptible to redox stress (Figure 7) [198]. It is also possible that ROS mediate STIM translocation and SOCE activation indirectly, through redox activation of ER Ca 2+ regulators IP 3 R and SERCA, which are also redox sensitive (See section 4).…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
“…It was shown that prostate cancer cell lines have a higher ratio of ORAI1/ORAI3 compared to primary human prostate epithelial cells [198]. The authors went on to show that an increased ORAI1/ORAI3 ratio makes prostate cancer cells more redox sensitive to SOCE inactivation by H 2 O 2 [198].…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
See 3 more Smart Citations